Identitas nasional dan Pancasila: Fondasi jati diri bangsa Indonesia di era modern - Tamim, Muhammad Husni (Maliki Interdisciplinary Journal, 2026)
National identity represents the uniqueness of a nation that distinguishes it from other nations in the world. For Indonesia, this identity is inseparable from the values ​​embodied in Pancasila, which serves as the foundation of the state and a guideline for the people’s lives. This article aims to analyze the role of Pancasila as a primary pillar in building Indonesia’s national identity and examine the challenges that arise in maintaining its existence amidst the rapid flow of globalization. Using a descriptive-analytical approach, this discussion explores the close relationship between Pancasila’s values ​​and the ongoing process of national character formation. This study concludes that Pancasila is not merely a formal symbol, but also a value system that remains relevant as a unifying force and a foundation for the formation of the Indonesian national personality.